Indeks Keanekaragaman Makrozoobentos Sebagai Bioindikator Tingkat Pencemaran Di Muara Sungai Jeneberang (Diversity Indices Makrozoobentos as Bioindicator Pollution Levels in Estuary of Jeneberang River) - Rachmawaty, Rachmawaty (bionature, 2011)
Makrozoobentos living relative lived, so it was better used as a guide environmental quality, as always contact with the waste into their habitat. Bivalvia and gastropod the most widely used as bioindicator pollution because he lived. This study aimed to know the level of species diversity in the estuary in estuary of Jeneberang River, to know the abundance of mollusks and know the type of mollusks that dominate in estuary of Jeneberang River. This research was descriptive of how diversity in estuary of Jeneberang River. The results obtained based on the diversity index showed <1.0, showed estuarine of Jeneberang River including heavy polluted waters. Based on the dominance index gained value approaching zero, then there is no dominant species.Key words: Makrozoobentos, Bivalvia, Gastropoda, Jeneberang River.